From Rage to Resignation: Reading Tina Mabry’s Mississippi Damned as a Post–Civil Rights Response to Nina Simone’s “Mississippi Goddam” - Moore, Marlon Rachquel (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Much has been written about Nina Simone’s song “Mississippi Goddam” because it lyrically achieves the political consciousness of the embattled community whose experiences and energy it intends to speak to, through, and for. With its curse words, impatient tone, and energetic rhythm, it could never be mistaken for the traditional, Christian-inflected civil rights dirge. “Alabama’s got me so upset,” the chorus complains. “Tennessee made me lose my rest, and,” as if its atrocities need not be spelled out, “every body knows about Mississippi, goddam!” The song was banned from radio airplay but still became part of the civil rights sound
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé